2016
DOI: 10.1177/1556264616668974
|View full text |Cite
|
Sign up to set email alerts
|

Getting It “Right”

Abstract: Getting It ‘Right’: Ensuring Informed Consent for an Online Clinical Trial Ethical principles in conducting technology-based research require effective and efficient methods of ensuring adequate informed consent. This study examined how well participants understood the informed consent form for an online postpartum depression trial. Pregnant women (N=1,179) who consented to the trial demonstrated an understanding of the purpose (86.1%) and procedures of the study (75.8%); and the minimal risks associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Studies varied in their participants' characteristics as they targeted selected groups (Table 1). Mean age was reported in 10 studies, ranging from 27 to 73 years (39)(40)(41)(42)(43)(44)(45)(46)(49)(50). Two studies did not provide mean age of participants (47)(48).…”
Section: Study Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies varied in their participants' characteristics as they targeted selected groups (Table 1). Mean age was reported in 10 studies, ranging from 27 to 73 years (39)(40)(41)(42)(43)(44)(45)(46)(49)(50). Two studies did not provide mean age of participants (47)(48).…”
Section: Study Participantsmentioning
confidence: 99%
“…Level of education was reported in nine studies, with three reporting no formal education in the majority of their sample (45,47,48). The remaining six studies reported educational level ranging from university to college education (40) (43-44) (46) (49)(50).…”
Section: Study Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…We will make every effort to secure written records of informed consent with wet signatures, but a flexible approach may be necessary in the absence of face-to-face interactions. [76][77][78][79] Table 2 describes our preparations to facilitate recruitment without undue loss of fidelity to ethical principles of voluntary participation, research integrity and transparency. 79 80 data collection in work package 1: individual interviews The study team will liaise with each prospective and consented participant by email, telephone, SMS and/ or post to arrange a mutually convenient opportunity for semistructured interview via telephone within our work package 1.…”
Section: Open Accessmentioning
confidence: 99%